PENGARUH MEDIA CROSSWORD PUZZLE TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS V SD - Aprilia, Riza Dwi; Kusuma, Rendra Sakbana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
ABSTRACT This study aims to find out whether there is an influence on the level of independence of students with crossword puzzle media in the science and science subject of class V division material at SDN Lenteng Timur 1 Sumenep with this quantitative research using the research design used is pre-Experimental Designs. The sample used by class V students was 30 students in total. The instruments used are in the form of pretest and posttest questions. Meanwhile, the analysis tests are validity, reliability, and t-test sample tests with the help of the IBM SPSS v21.0 application. This is proven by using crossword puzzle media The level of students' critical thinking ability was obtained significantly (2-tailed) of 0.000 < 0.05 which stated that there was a difference in the level of thinking of students using crossword puzzle media.